Keefektifan Pendekatan Konstruktivisme Dalam Pelatihan Implementasi Strategi Pembelajaran Bahasa Bagi Guru Mata Pelajaran Bahasa Dayak Ngaju - Iwan Fauzi; Dina Mardiana; Akhmad Syifa Ramadhani; Ririn Mahdiyani Safutri (FKIP, Universitas Palangka Raya, 2021)
This study aims to analyze the effectiveness of the constructivism approach in training to the implementation of the language learning strategy for teachers of Dayak Ngaju language at SD Muhammadiyah Pahandut and SDN-5 Panarung, Kota Palangkaraya. Six teachers from SD Muhammadiyah Pahandut and SDN-5 Panarung were selected as the sample by using purposive sampling technique from the total population. This study used a quantitative method with an experimental design model of one group pretest-posttest design. From the result of the data analysis using the Wilcoxon statistical test, it can be concluded that the constructivism approach is effectively used in training the teachers by the implementation of the language learning strategy in teaching Dayak Ngaju language subject in both primary schools. This is depicted by the teachers’ attainment on the pretest score was 62.5 and the attainment in the posttest reached 81.6 where the significance test result in the statistical analysis shows the Sig.value of p < 0.05 so that Ho is rejected.